THE USE OF DUBBING VIDEO TECHNIQUE TO IMPROVE STUDENTS’ SPEAKING SKILL AT SMPN 35 MAKASSAR - Haerunnisa Haerunnisa; Dahlia D. Moelier; Ulfah Syam (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2021)
This study aimed to find out the improvement of the students speaking skill through implementation dubbing video technique at SMPN 35 Makassar academic year 2020/2021. This study used pre-experimental design with pre-test, treatment, post-test and data analyzed. The data was collected and analyzed from several recording voice from the students in the English classroom. The population of this research was second grade from class VIII.2 which consist 20 students as a sample. This study indicated the result of the used of voice notes and dubbing video short animation movie to improve students’ speaking skills by data analyzed from accuracy and fluency. And the result indicated mean score in pre-test was 56.15 and mean score in post-test was 87.45, it means that was influenced the improvement of students’ speaking skill.